Forests in International Law Is There Really a Need for an International Forest Convention? - Eikermann, Anja.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book investigates the potential need for an international convention on forests and establishes a multifunctional concept of forests as a cornerstone for international forest regulation. Accordingly, it examines a variety of international instruments pertaining directly or indirectly to forests and explores their entangled, fragmented nature. While contending that the lack of consistency in international law impedes the development of a stand-alone international forest convention, at the same time it argues that the lessons learned from fragmentation as well as from the history of forest discourse on the international level open up new options for the regulation of forests in international law, based on (new) concepts of coordination and cooperation.
State of Research and Structure of the Book -- The Case for International Forest Regulation – The Benefits and Challenges of the Multifunctional Concept of Forests -- Agenda-Setting and Institution Building for Forests – Entangled Structures and the Failure of Legalization -- The Treaty Canopy – General, International Environmental and International Economic Law Covering Forests -- The Options for an International Regulation of Forests -- Conclusions -- Summary.
Keywords: International environmental law; Environmental law; Environmental policy; Forestry management; International Environmental Law; Environmental Law/Policy/Ecojustice.; Forestry Management